Univariate and bivariate distribution of growth traits in beef buffaloes from Brazil - Filho, R. M.; Malhado, C. H. Mendes; Ramos, A. de Amorim [UNESP]; Carneiro, P. L. Souza; Affonso, P. R. Antunes de Mello; Souza, J. C. de (Pagepress Publ, 2007)
The aim of this study was to analyze the weight at birth (BW) and adjusted at 205 (W205), 365 (W365) and 550 (W55O) days in beef buffaloes from Brazil, using two approaches: parametric, by normal distribution, and non-parametric, by kernel function, and thus estimating the genetic, environmental and phenotypic correlation among traits. Information of 5,169 animals at birth (BW), 3,792 at 205 days (W205), 3.883 at 365 days (W365) and 1,524 at 550 days of age (W550) were used. The birth weight distribution presented an evident discrepancy in relation to the normal distribution. However, W205, W365 and W550 presented normal distributions. The birth weight presented weak genetic, environmental, and phenotypic associations with the other weight measurements. On the other hand, the weight traits at 205, 365, 550 days of age showed a high genetic correlation.
Keywords: Normal distribution; Parameter; Scatter plot; Selection; Smoothing